The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1242/jcs.03492
|View full text |Cite
|
Sign up to set email alerts
|

MAP-kinase activity necessary for TGFβ1-stimulated mesangial cell type I collagen expression requires adhesion-dependent phosphorylation of FAK tyrosine 397

Abstract: The signals mediating transforming growth factor β (TGFβ)-stimulated kidney fibrogenesis are poorly understood. We previously reported TGFβ-stimulated, Smad-mediated collagen production by human kidney mesangial cells, and that ERK MAP kinase activity optimizes collagen expression and enhances phosphorylation of the Smad3 linker region. Furthermore, we showed that disrupting cytoskeletal integrity decreases type I collagen production. Focal adhesion kinase (FAK, PTK2) activity could integrate these findings. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
52
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 68 publications
7
52
1
Order By: Relevance
“…ERK-mediated regulation of Smad signaling is of particular interest due to a specific series of serines and threonines in the Smad linker region that are the targets for ERK, although the function of these phosphorylation events remains yet to be fully uncovered (3,13). In the above mentioned study, we found that a Y397F FAK mutant inhibited ERK activity and ERK-mediated Smad linker region phosphorylation as well as inhibiting collagen production (9), suggesting that integrin engagement-dependent ERK activity via FAK is necessary for the maximal collagen response to TGF-␤1.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…ERK-mediated regulation of Smad signaling is of particular interest due to a specific series of serines and threonines in the Smad linker region that are the targets for ERK, although the function of these phosphorylation events remains yet to be fully uncovered (3,13). In the above mentioned study, we found that a Y397F FAK mutant inhibited ERK activity and ERK-mediated Smad linker region phosphorylation as well as inhibiting collagen production (9), suggesting that integrin engagement-dependent ERK activity via FAK is necessary for the maximal collagen response to TGF-␤1.…”
mentioning
confidence: 65%
“…In seeking a common mediator for several signaling pathways that we have previously identified to play roles in TGF-␤ induction of ECM accumulation in renal cells (6 -8), we recently reported that integrin engagement-mediated activation of focal adhesion kinase (FAK) is required for TGF-␤1-induced type I collagen production (9). FAK serves as a molecular "dock," recruiting additional signaling molecules, such as Src family tyrosine kinases (10), for which FAK Tyr-397 phosphorylation subsequent to integrin engagement is critical (11).…”
mentioning
confidence: 99%
“…[25][26][27][28] We had previously identified Egr-1 as a novel TGF-␤ mediator with a significant role in collagen regulation. 10 Whereas induction of Egr-1 by acute injury has been investigated extensively, its regulation by Regulation 4 TGF-␤ in the context of fibrogenesis and its role in fibrosis remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…8H). We previously showed that Rho-kinase mediated stretch-induced Erk activation, and Erk may modulate Smad3 transcriptional activity through phosphorylation on the Smad3 linker region (Hayashida et al, 2007;Krepinsky et al, 2005b). Fig.…”
Section: Stretch-induced Smad3 Activation Is Regulated By Rac1/ Pak1 mentioning
confidence: 95%